An awareness on online gaming addiction and its impact on physical health among undergraduate students IIUM Kuantan campus - Abdul Hamid, Siti Hazariah; Kamaruddin, Ahmad Firdaus; Ellin, Mohammed Rasheedan; Romzati, Romzati (ACADEMIC INSPIRED NETWORK, 2024)
Movement Control Order (MCO) in Malaysia and many parts of the world to break the chain of COVID-19 pandemic led to the student involvement in social media in particular online gaming. This study is aimed to determine the level of awareness on online gaming addiction & its association on physical health among undergraduate students in one of public university in Pahang Malaysia. This cross-sectional study was conducted among 244 undergraduate students from February to June 2023. The data were analysed by using Mann Whitney and Kruskal Wallis Test. The result shows that undergraduate students in this study have a good awareness of online gaming addiction and a good impact on physical health. There is a significant difference between addiction level on online gaming and impact on physical health. However, level of awareness has no significance different from the addiction level of the undergraduate student IIUM Kuantan. There is no significant association between sociodemographic background with the awareness on online gaming addiction and its impact on physical health. As a conclusion, it is deemed necessary to review current addiction level on online gaming instead of their awareness on online gaming addiction & physical health to the students and to ensure their professional readiness in the future. The university authority needs to address and be aware of gaming addiction that affects students’ physical and mental health. Initiatives are needed to support and help students overcome and avoid this issue to improve their health performance.